2008
DOI: 10.1099/mic.0.2007/015289-0
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus host specificity: comparative genomics of human versus animal isolates by multi-strain microarray

Abstract: Staphylococcus aureus is a commensal and pathogen of several mammalian species, particularly humans and cattle. We aimed to (i) identify S. aureus genes associated with host specificity, (ii) determine the relatedness of human and animal isolates, and (iii) identify whether human and animal isolates typically exchanged mobile genetic elements encoding virulence and resistance genes. Using a well-validated seven-strain S. aureus microarray, we compared 56 UK S. aureus isolates that caused infection in cows, hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
236
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(257 citation statements)
references
References 36 publications
18
236
1
2
Order By: Relevance
“…SIRU05 was analyzed more in depth, since it could not be amplified in any of the bovine isolates including 4 isolates with ST97 that were already known as possibly human derived (Smith et al, 2005a;Sung et al, 2008). PCR of the region neighboring SIRU05 demonstrated that all isolates were fragment A and B positive.…”
Section: Discussionmentioning
confidence: 99%
“…SIRU05 was analyzed more in depth, since it could not be amplified in any of the bovine isolates including 4 isolates with ST97 that were already known as possibly human derived (Smith et al, 2005a;Sung et al, 2008). PCR of the region neighboring SIRU05 demonstrated that all isolates were fragment A and B positive.…”
Section: Discussionmentioning
confidence: 99%
“…Some sequence types (ST) such as ST398 are found in many host species, including humans and animals (Weese and van Duijkeren, 2010), whereas other types of Staph. aureus are specifically associated with animals (Sung et al, 2008;Ikawaty et al, 2009;Lowder et al, 2009). Bovineassociated Staph.…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that over 60% of the emerging human pathogens come from animals [1] and food products [2]. The minority of S. aureus strains obtained from food products are not host specific and consumption of these contaminated feed leads to colonization of S. aureus in humans causing community acquired infections [3][4][5]. In addition, developed resistance to methicillin limits the use of β-lactam antimicrobials and the antibiogram schemes were often uninformative for typing many strains [6].…”
Section: Introductionmentioning
confidence: 99%